Effect of grain structures and precipitation characteristics on the corrosion behaviour of Sc-containing Al-Cu-Li alloy. (19th May 2023) - Xie, Yuankang; Liu, Shengdan; Deng, Yunlai; Guo, Xiaobin
ABSTRACT: The intergranular corrosion behaviour of Al-Cu-Li-Sc alloy with different microstructures was systematically investigated in this work. The SKPFM characterisation revealed that the AlCuSc (W) phase has more negative potential compared to the Al matrix and undergoes dealloying in the intergranular corrosion solution. The dealloying rate of the W phase in the corrosive solution is relatively slow, which does not lead to serious pitting characteristics. As denser anodic T1 precipitates formed on low-angle grain boundaries of the partially recrystallised sample will reduce the precipitates on the sub-grain interior, resulting in the low-angle boundary being prone to preferential corrosion and reduced intergranular corrosion resistance. The complete recrystallised sample exhibits corrosion of grain interior and propagates along corroded bands parallel to 111Al habit planes of T1 precipitates, reducing the expansion rate of corrosion along the grain boundaries. Restraining the IGC along the low-angle grain boundary and inducing crystallographic corrosion to improve the intergranular corrosion resistance.